Tumor infiltrating lymphocytes and survival in patients with head and neck squamous cell carcinoma. Issue 7 (16th February 2016) - Nguyen, Nghia; Bellile, Emily; Thomas, Daffyd; McHugh, Jonathan; Rozek, Laura; Virani, Shama; Peterson, Lisa; Carey, Thomas E.; Walline, Heather; Moyer, Jeffery; Spector, Matthew; Perim, Daniel; et al.
Abstract: Background: Because immune responses within the tumor microenvironment are important predictors of tumor biology, correlations of types of tumor infiltrating lymphocytes (TILs) with clinical outcomes were determined in 278 patients with head and neck squamous cell carcinoma (HNSCC). Methods: Infiltrating levels of CD4 (helper T cells), CD8 (cytotoxic/suppressor T cells), FoxP3 (regulatory T cells), CD68 (myeloid‐derived suppressor cells, ) and CD1a (Langerhans) cells were measured in tissue microarrays (TMAs). Cox models tested associations with patient outcomes after adjusting for all known prognostic factors. Median follow‐up was 36.6 months. Results: Higher CD4 and CD8 TIL levels were associated with improved overall survival (OS; hazard ratio [HR] = 0.77; 95% confidence interval [CI] = 0.65–0.93; p = .005 and HR = 0.77; 95% CI = 0.64–0.94; p = .008, respectively), and relapse‐free survival (RFS; p = .03 and .05, respectively). After controlling for prognostic factors, higher CD4 levels predicted improved OS and disease‐specific survival (DSS; p = .003 and p = .004, respectively). Conclusion: The findings suggest that TILs are a significant independent prognostic factor for HNSCC that differ by treatment. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1074–1084, 2016